ANALISIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS E-LEARNING MELALUI APLIKASI QUIZIZZ KODE QR PADA PEMBELAJARAN IPAS DI SD - Sawitri Ayuningtyas; Oktiana Handini; Elinda Rizkasari (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This research aims to analyze the implementation of the Problem-Based Learning (PBL) model based on e-learning using the Quizizz application with QR codes in IPAS (Science, Social Studies, Arts, and Culture) learning at SD Negeri Karangasem 1 Surakarta. The background of this research is the challenge of creating interactive and relevant IPAS learning in the digital era, as well as the potential of technology to enhance student engagement. The research method employed is descriptive qualitative with a case study approach. Data collection was conducted through observation, interviews, and documentation. The subjects of the study were teachers and fourth-grade students at SD Negeri Karangasem 1 Surakarta. The results show that the implementation of PBL based on e-learning with Quizizz QR codes was effective in increasing student motivation and conceptual understanding. Students showed high enthusiasm in solving presented problems, and the use of QR codes facilitated access to interactive quizzes, encouraging independent learning and collaboration. However, some obstacles were identified, such as limited access to devices and internet networks for some students. The implications of this research highlight the importance of developing learning tools that are adaptive to school conditions and the availability of student technological facilities. This study recommends using a combination of online and offline methods to overcome these limitations, as well as continuous training for teachers in utilizing learning technology.